Community Resilience of PKH Beneficiaries Post-COVID-19 Pandemic in Metro City - Ita Prihantika; Rahayu Sulistiowati; Nana Mulyana (Journal of Research in Social Science and Humanities, 2026)
This study examines the community resilience dimensions of beneficiary families (Kelompok Penerima Manfaat or KPM) of the Family Hope Program (Program Keluarga Harapan) in Metro City, Lampung Province, Indonesia, following the COVID-19 pandemic. Using a qualitative approach with the Most Significant Change (MSC) technique, data were collected through in-depth interviews with PKH social companions and P2K2 (Pertemuan Peningkatan Kemampuan Keluarga) coordinators, complemented by observation and documentation. The finding reveals four key resilience attributes among KPM: (1) adaptive mechanisms during the pandemic, including leveraging government assistance, asset liquidation, and livelihood diversification; (2) socio-economic transformation evidenced by children's educational advancement and growing economic independence; (3) social and spiritual capital as foundational resilience resources; and (4) mindset shifts facilitated by P2K2 monthly empowerment sessions. The study shows that while PKH's conditionality structure and companion-based mentoring have contributed to observable resilience, inconsistent sanction enforcement and recipient reluctance to exit the program remain key challenges. Recommendations include strengthening program consistency, expanding practical economic skills training, integrating digital marketing, and promoting household-level food self-sufficiency.